Determination of Audit Report Lag in Transportation Companies on the Indonesia Stock Exchange - Rukmana, Meilisa; Muniroh, Hetty (Universitas Nusantara PGRI Kediri, 2025)
The purpose of this activity is to demonstrate how the delay in audit reports for transportation businesses listed on the IDX from 2020 to 2022 is influenced by age, size, financial health, and operational complexity. This study uses a quantitative approach with independent variables such as operational complexity, financial health, company size, and company age, while the dependent variable is the audit report lag. The research data is secondary data in the form of documentary data accessed through the official IDX website, www.idx.co.id, using purposive sampling method. There are 15 modes of transportation used by the population. A total of 45 observations from fifteen companies were used as the research sample. Multiple linear regression analysis serves as the data analysis method. This study found that the age of the company and the size of the company partially have no significant impact on audit report lag, while the financial condition and operational complexity variables partially have no significant effect on audit report lag. The results of this study can be beneficial for the stream of literature related to company age, company size, financial condition, and operational complexity.